Digital games platforms: a literature review, an empirical assessment of quality and exclusivity in video-game market and a study on project management. - Higuchi, Marcelo Makoto (2018)
Digital games are part of the creative industries, which is based on value creation through ideas and creativity. This market has gained relevance due to technology development that attracted both new firms and users. The present dissertation aims to explore three themes: (1) video game market as a two-sided market; (2) the effects of characteristics and behavior of game titles on consoles sales; and (3) project management to develop digital games. Those themes were explored through three articles: the first is a literature review and a bibliometric study of the economic concepts on two-sided market, which focused at identifying main topics, research trends and avenues for futures research. The second text is an analysis on the simultaneous influence of games\' quality and exclusivity on console sales. The last one is a qualitative, multiple-case study to understand, explore and suggest improvements to game project management in the Brazilian market. Findings include: (1) the main authors and topics, trends and developments, from and avenues for future research; (2) combinations of quality and exclusivity can affect console sales either positively or negatively, (3) quality has a predominant effect on sales over games non-exclusivity; and (4) the use of agile methodologies and Design Thinking are diffused among game developers.